Case Study Of Mindvalley Labs Sdn Bhd - Gorji, Fatemeh Rahimi (2008)
This study aims at showing the role of effective Internet marketing techniques in the success of a small startup company. The study focuses on MindValley Labs Sdn. Bhd which started its operations in 2002 in the self-development industry and became profitable in a span of few months.